Infrastructure and trade - Hildegunn Kyvik Nordås; Roberta Piermartini (World Trade Organization (WTO), 2004)
This paper explores the role that quality of infrastructure has on a country's trade performance, estimating a gravity model that incorporates bilateral tariffs and a number of indicators for the quality of infrastructure. The paper looks at the impact of the quality of infrastructure (road, airport, port and telecommunication, and the time required for customs clearance) on total bilateral trade and on trade in the automotive, clothing and textile sectors. In order to obtain unbiased estimators, multilateral resistances for tariffs and remoteness are introduced in the gravity equation. Moreover, the robustness of the results is tested by estimating a fixed-effect model, where bilateral indexes of the quality of infrastructure are included. The results can be summarised in four main findings: (i) bilateral tariffs, generally neglected in gravity regression of bilateral flows, have a significant negative impact on trade; (ii) quality of infrastructure is an important determinant of trade performance; (iii) port efficiency appears to have the largest impact on trade among all indicators of infrastructure; (iv) timeliness and access to telecommunication are relatively more important for export competitiveness in the clothing and automotive sector respectively.
Keywords: F13; F17; 330; trade; infrastructure; gravity model; resistance terms; tariffs; WTO